THE EFFECT OF BRAND IDENTIFICATION AND BRAND IMAGE ON BRAND LOVE AND BRAND LOYALTY ON IPHONE SMARTPHONE PRODUCT USERS IN SAMARINDA - Aulia Fitriani; Gusti Noorlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze and explain the influence of Brand Identification and Brand Image on Brand Love and Brand Loyalty on Iphone Smartphone Product Users in Samarinda. The population in this study used the iPhone smartphone product more than once. The sampling technique used was non-probability sampling with the purposive sampling method with a total sample of 100 people. Data collection techniques using questionnaires. The analysis was carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9 and using SPSS Version 25 to test the validity and reliability of the respondents. The results of this study indicate that the influence of Brand Identification has a positive and significant effect on Brand Love; the influence of Brand Image has a positive and significant effect on Brand Love; the effect of Brand Identification has a positive but not significant effect on Brand Loyalty; the effect of Image has a positive but not significant effect on Brand Loyalty; the influence of Brand Love has a positive and significant effect on Brand Loyalty. Keywords : Brand Identification, Brand Image, Brand Love, and Brand Loyalty.